Proactive scheduling for situated displays - Ribeiro, Fernando Reinaldo (2007)
We present an approach to improve the usefulness of situated displays systems. Our approach is based on expected utility obtained by presenting each job. We use MAUT to specify job utility and a context-aware scheduler to select the most relevant job. In our future work we will proceed with simulations in order to refine utility functions and typical weight vectors. We also intend to deploy the system with users and create a feedback panel that can function as an actionable for any type of job, and thus provide essential data for evaluating scheduling policies.